1991
DOI: 10.1088/0143-0815/12/4/009
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the effect of the third dimension on a two-dimensional electrical impedance tomography system

Abstract: This work is based on the Applied Potential Tomography (APT) system developed in Sheffield and the results specifically relate to this system. Using a cylindrical phantom containing saline, the effects of extended layers in the third dimension on the two-dimensional tomographic images have been studied. Experimentally obtained magnitudes of pixel values corresponding to different conditions in the third dimension are presented. Analysis of these data brings out two phenomena: (i) layers of changed resistivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 2 publications
1
56
0
Order By: Relevance
“…EIT is sensitive to periodic and non-periodic changes in electrical tissue conductivity in a slice with a vertical thickness roughly half the chest width 26. An increase in intrapulmonary gas volume decreases conductivity, while increased blood or fluid volume or disruption of cellular barriers raise it.…”
Section: Raw Eit Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…EIT is sensitive to periodic and non-periodic changes in electrical tissue conductivity in a slice with a vertical thickness roughly half the chest width 26. An increase in intrapulmonary gas volume decreases conductivity, while increased blood or fluid volume or disruption of cellular barriers raise it.…”
Section: Raw Eit Imagesmentioning
confidence: 99%
“…26 An increase in intrapulmonary gas volume decreases conductivity, while increased blood or fluid volume or disruption of cellular barriers raise it.…”
Section: Raw Eit Imagesmentioning
confidence: 99%
“…To overcome this difficulty Electrical Impedance Tomography (EIT, initially termed Applied Potential Tomography -APT) was developed [2] which uses a number of electrodes, typically 8, 16 or 32 fixed transversely around a cylindrical volume in a particular plane, to image the 2 dimensional conductivity distribution in the said plane. However, since current flows in 3D, there is significant contribution to the image from points in the 3 rd dimension in a complex way [3], [4]. Thus the individual pixel values of the image do not give the right point sensitivity as expected.…”
Section: Imentioning
confidence: 85%
“…This is because changes in relative ΔZ synchronous with the heart rate occur in the heart atria and ventricles as well as in large vessels, and not only in the lungs. Moreover, the spatial resolution of EIT scans is low, and the scans are slightly distorted with respect to anatomy and reflect changes in electrical impedance occurring in regions above and below the electrode plane [41]. In an early attempt to assign the registered changes in intrathoracic electrical impedance to known anatomical structures, it was concluded that EIT could hardly distinguish the heart chambers and blood vessels [16].…”
Section: Discussionmentioning
confidence: 99%